Special Issue on the Application of Active Noise and Vibration Control - Yijing Chu; Ming Wu; Hongling Sun (Applied Sciences, 2022)
Active noise and vibration control aims at attenuating unwanted sound or vibration by automatically generating an anti-sound or vibration [...]